An application of Taguchi experiment design methods on optimization of mortar mixture composition with Silica Fume as a partial substitute for cement. (January 2020) - De Side, G N; Kencanawati, N N; Hariyadi
Abstract: The development of concrete technology in infrastructure also triggers the progressive cement manufacture, where cement production also contributes significantly to the emission of CO2 . To minimize the use of cement and increase mortar quality, the addition of additive substance material is needed with a quality control method. The purpose of this research is to establish the proportions of the materials with the optimum partial replacement of cement by silica fume to the compressive strength and physical properties of the 56 days old mortar using Taguchi Method design of experiment. This research uses 3 factors, which are silica fume proportion, sand proportion, and cement proportion. Each factor consists of 3 levels, with silica fume content is ±20% from the total weight of the cement. The mortar is based on 9 combinations of materials on the orthogonal matrix L9(3 4 ) created with dimensions of 50 x 50 x 50 mm cube. The results show that the optimum proportion is 150 gr of silica fume, 660 gr of cement and 1400 gr of sand which is equivalent to replacing 18.52 % cement with silica fume, which gains 54.00 MPa compressive strength, pH 9.75 and 5.369 % water absorption.